Exploring the age and gender-based distribution of paranasal sinus osteomas using cone beam computed tomography: A retrospective cross-sectional study - Zeliha Merve Semerci; Sevcihan Günen Yılmaz (Heliyon, 2024)
Objective: The objective of this study is to explore the prevalence, size, location and radiographic features of osteomas in the paranasal sinuses using cone beam computed tomography imaging. Study design: This study was planned as retrospective cross-sectional. 499 consecutive cone beam computed tomography scans obtained in a dentomaxillofacial radiology department for various dental indications. Statistical analysis of all data was done with SPSS version 22. Descriptive statistics and chi-square tests were used to determine the prevalence of categorical parameters. Results: Osteoma was detected in 7 % (n = 35) of the 499 images analyzed. The age of the patients ranged from 6 to 96 years (mean 42.03 ± 18.70). No significant difference was found between the genders (p = 0.77). In terms of localization, it was significantly more common in the ethmoid sinuses (p < 0.01). Cortical type osteoma was observed the most frequently in the analyzed images (p < 0.01). The incidence of osteoma was not significant depending on age (p = 0.50). Conclusion: Osteomas in the paranasal sinuses show a 7 % prevalence in CBCT images, with the ethmoid sinus being the most common site. The average size of osteomas was 3.43 ± 1.78 mm, predominantly cortical in type. These findings highlight the necessity for thorough examination of CBCT images by dentomaxillofacial radiologists to avoid overlooking osteomas.